Thinking with Kant's "Critique of judgment" - Chaouli, Michel (Cambridge, Massachusetts [u.a.] : Harvard University Press, 2017)
In this book, Michel Chaouli aims to inhabit Kant's work, to "know the text from inside" and to reveal the strangeness, audacity, and "blissful" potential of its claims. Chaouli lays out the major concepts that run beneath Kant's Third Critique, assuming no prior knowledge of Kant, while simultaneously aiming to offer original interpretations of aspects of Kant's thinking. Chaouli's background is in comparative literature, and his insights are often drawn from close readings that reveal how Kant's language supports, and sometimes resists, the philosopher's claims. The majority of Chaouli's text is devoted to Kant's aesthetic theory, from the first chapter, "Pleasure," which examines pleasure's central role in aesthetic experience for Kant, to the sixth chapter, "Aesthetic Ideas," which suggests that the concept of aesthetic ideas that arises late in Kant's text occasions a rethinking of much that has preceded it. Chaouli's final chapters turn toward the second, distinct section of the Critique of Judgment: Kant's teleological theory of life. Chaouli shows how Kant's teleology echoes and enriches his aesthetic theory and suggests that teleological philosophy is still relevant today--not in the way that it is often wielded on both sides of the intelligent design debate, but rather as a description of one ineradicable aspect of the human understanding of organic life.--
Literaturangaben
Keywords: Ästhetisches Urteil; Kant, Immanuel; Kant, Immanuel